Image and Substance Failures in Regional Organisations: Causes, Consequences, Learning and Change? - Meng Hsuan Chou; Michael Howlett; Kei Koga (Politics and Governance, 2016)
States often pool their sovereignty, capacity and resources to provide regionally specific public goods, such as security or trade rules, and regional organisations play important roles in international relations as institutions that attempt to secure peace and contribute to achieving other similar global policy goals. We observe failures occurring in these arrangements and activities in two areas: substance and image. To analytically account for this, we distinguish four modes of substance and image change and link these to specific types of failure and (lack of) learning. To empirically ground and test our assumptions, we examine instances of image failure in ASEAN (political/security policy) and substantive policy failure in EU labour migration policy. In so doing, this article contributes to several different fields of study and concepts that have hitherto rarely engaged with one another: analyses of policy failure from public policy, and regional integration concerns from area studies and international relations. We conclude with suggestions for ways forward to further analyse and understand failures at the international and supranational levels.